Fostering Aesthetic Sensitivity and Artistic Skills through Visual Arts in Secondary School Students - G‘aybullayeva Mehribon G‘olibovna (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Abstract: This article examines the role of visual arts education in fostering aesthetic sensitivity and artistic skills among secondary school students. Visual arts provide students with opportunities to explore color, form, and composition while developing creative thinking and problem-solving abilities. The study emphasizes pedagogical strategies, including interactive lessons, project-based learning, and digital tools, to enhance students’ artistic development. Research by Shovdirov S. A. and other scholars forms the theoretical foundation of the discussion.